The ecology of sodic sites in the Eastern Transvaal Lowveld - Chappell, Clive (My University, 1992)
The effect of sodium on clays dominates the formation and ecology of granitic eatenas in the Eastern Transvaal Lowveld. This study reviews the process involved and explains the soil, vegetation and erosion patterns in this landscape. Weathering parent rock gives rise to sodium in sufficient amounts to promote clay dispersion. Dispersed, mobile, clays respond to seasonal pulses of laterally moving soil water resulting in alternating zones of clay illuviation and clay deposition down hillslopes [Abbreviated Abstract. Open document to view full version]
Submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg as a requirement for the Degree of Master of Science. Johannesburg, 1992.
Keywords: Ecology; Soil surveys--Geophysical methods--South Africa--Transvaal; Soils--Sodium content; Ecology; Soil erosion--South Africa--Transvaal